An efficient identification scheme based on Bivariate function hard problem - Boon, Chian Tea; Kamel Ariffin, Muhammad Rezal; Abd Ghafar, Amir Hamzah; Sapar, Siti Hasana; Mohamat Johari, Mohamat Aidil (Multidisciplinary Digital Publishing Institute, 2022)
Symmetric cryptography allows faster and more secure communication between two entities using the identical pre-established secret key. However, identifying the honest entity with the same secret key before initiating symmetric encryption is vital since the communication may be impersonated. Tea and Ariffin, in 2014, proposed a new identification (ID) scheme based on the Bivariate Function Hard Problem (BFHP) that proved secure against impersonation under passive, active and concurrent attacks via the BFHP-hardness assumption. In this paper, we upgrade the ID scheme and improve some of its settings. Next, we provide the security proof against impersonation under active and concurrent attacks in the random oracle model via the hardness assumption of the One-More BFHP. Finally, we include an additional discussion about the computational efficiency of the upgraded ID scheme based on BFHP and present its comparison with other selected ID schemes.